Analysis of Customer Preferences and Customer Attitudes on Islamic Banks - Chandra Warsito (Postgraduate Program, State Institute on Islamic Studies Purwokerto, 2021)
The Purpose of this study is to evaluate the difference between customer preferences and customer attitudes of Islamic Bank in Ex-Banyumas residency of Central Java, Indonesia. It also evaluates the most considers attributes in choosing an Islamic bank. Accidental sampling is used in this study with a total of respondents as 100. To observe the difference in customer preferences, the scoring method and Chi-Square analysis are applied, meanwhile, Fishbein’s Attitude model is used to discover the customer attitudes. It is concluded that there is a significant difference in customer preferences on choosing Islamic banks on Ex-Banyumas residency, particularly when it is based on gender and long-period of customer status. It also revealed that customers’ decision in choosing Islamic banks is influenced by service quality. The findings of this study could give valuable input to Islamic bank management in the improvement in their services. This study is explaining the implementation of the Islamic principle in banking operational activities, as in fact the main reason for most customers to get services from the Islamic bank. This study is also enriched the Islamic banking studies in Indonesia.